Uji Efektivitas Ekstrak Albumin Daging Belut (Monopterus albus) Secara In Vivo Terhadap Luka Sayatan pada Mencit Jantan (Mus mucullus L.) - Mahral Effendi Sembiring; Sari Dhiya Ulhaqqi (Herbal Medicine Journal, 2026)
Incision wounds are tissue injuries that can disrupt skin function and require an optimal healing process. One of the efforts to accelerate wound healing is through the use of natural ingredients rich in protein and albumin, such as eel meat (Monopterus albus). This study aimed to evaluate the in vivo effectiveness of eel meat extract on topical incision wound healing in male mice (Mus musculus L.) and to determine the most effective concentration. The study was conducted on 25 male mice divided into five treatment groups: negative control (ointment base), positive control (Betadine ointment), and eel meat extract at doses of 0.2 g, 0.4 g, and 0.5 g. Treatments were applied topically twice daily for 12 days. Data were analyzed using one-way ANOVA followed by a Post Hoc test. Eel meat extract was shown to contain albumin protein, which plays a role in accelerating wound healing. Topical application of the extract promoted faster wound closure, with the 0.5 g dose achieving complete closure by day 9, compared to day 12 in the negative control and day 11 in the positive control. Statistical analysis revealed no significant differences on day 3, but highly significant differences were observed on days 6 and 9 among the treatment groups. Eel meat extract (Monopterus albus) is effective in accelerating incised wound healing in male mice, with the 0.5 g dose showing the most optimal results.